1998
DOI: 10.1016/s0304-3959(97)00224-8
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence of the association between the presence of musculoskeletal pain and physical disability in community-dwelling senior citizens

Abstract: The proportion of people 65 years of age and older who report musculoskeletal pain and physical disability is high. The main objective of this study was to determine whether physical disability was associated with the presence of musculoskeletal pain in a sample of senior citizens. Self-administered questionnaires were sent to a sample of 1306 community-dwelling senior citizens in London, Ontario, Canada between August and October 1995. The questionnaire included questions about pain, difficulty performing act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 20 publications
6
85
0
2
Order By: Relevance
“…The co-occurrence of different causes of disability in more than two-thirds of the cases supported our decision of using general syndromes in the case definition, which allowed for an easy definition of the cases, even if some of them could be related to other nonmusculoskeletal problems. The specific diagnoses by GPs were mostly axial and peripheral osteoarthritis, followed by soft tissue problems and inflammatory diseases, as expected (2,8,16,24,25). The presence of a high Charlson index, a high level of pain, and associated MSD comorbidities reflects the spectrum of the more prevalent diseases at this age (26) and gives a clear idea of the complex management needed to improve the situation.…”
Section: Discussionsupporting
confidence: 62%
“…The co-occurrence of different causes of disability in more than two-thirds of the cases supported our decision of using general syndromes in the case definition, which allowed for an easy definition of the cases, even if some of them could be related to other nonmusculoskeletal problems. The specific diagnoses by GPs were mostly axial and peripheral osteoarthritis, followed by soft tissue problems and inflammatory diseases, as expected (2,8,16,24,25). The presence of a high Charlson index, a high level of pain, and associated MSD comorbidities reflects the spectrum of the more prevalent diseases at this age (26) and gives a clear idea of the complex management needed to improve the situation.…”
Section: Discussionsupporting
confidence: 62%
“…Functional limitations were shown in previous studies not only to increase with age, 4 but also to be more common among those in pain. 16,17 With higher age, fatigue, sleeping problems, and depressed mood also tend to be more prevalent and even more so among the elderly in pain (Table 4). Previous studies [11][12][13][14][15][16] report similar results.…”
Section: Discussionmentioning
confidence: 99%
“…4,11 When also affected by pain, these problems may have a major impact on daily life. [12][13][14][15][16][17] Despite this, the relationship between pain and these comorbidities has not been well studied among older people, and especially not among the oldest old. Ross and Crook 16 interviewed older people (n ϭ 66; mean age 79, range 64-99) and found that pain was associated with functional limitations, depression, impaired sleep, and low satisfaction with life.…”
Section: Introductionmentioning
confidence: 99%
“…There is, also, an age-related increase in the prevalence of arthritis [25], fibromyalgia [26] and trigeminal neuralgia [27]. This might be due to poor quality of life and increased probability of physical disability in older people [28]. Although almost all findings in the clinical literature are consistently pointed towards an increase in clinical pain with age [2,24,29,30], the effects of aging on pain perception remain unclear [16].…”
Section: Age Differences In Clinical Painmentioning
confidence: 99%